2008
DOI: 10.1038/ijo.2008.103
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and pulmonary function in the elderly: a 7-year longitudinal study

Abstract: Objective: To evaluate over a 7-year follow-up period the relationships between changes in body composition, fat distribution and pulmonary function in a sample of elderly men and women. Design: Longitudinal clinical study. Subjects: A total of 47 women and 30 men aged 71.6±2.3 and 71.7±2.2 years, respectively, at baseline with body mass index (BMI) values of 24.96 ± 3.28 and 27.04 ± 3.35 kg m À2 were followed for 7 years. Measurements: Body weight, waist circumference, sagittal abdominal diameter (SAD), fat-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 38 publications
(43 reference statements)
5
32
0
8
Order By: Relevance
“…In figure 1 [20][21][22][23]; 20 [18][19][20][21][22]; measured in subjects with younger, medium and older age respectively). However, the improvement of ACT observed after Omalizumab was lower in asthmatics over 65 years (20 [18-22]) when compared with younger subjects aged 18-39 years (24 [22][23][24][25]; p=0.039; figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In figure 1 [20][21][22][23]; 20 [18][19][20][21][22]; measured in subjects with younger, medium and older age respectively). However, the improvement of ACT observed after Omalizumab was lower in asthmatics over 65 years (20 [18-22]) when compared with younger subjects aged 18-39 years (24 [22][23][24][25]; p=0.039; figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…These different characteristics may increase disease severity and therefore reduce the response to treatment in the elderly. In fact, overweight/obese status, with an increased subcutaneous and visceral abdominal fat mass, which is a characteristics of elderly subjects, is a risk factor for a higher airway hyperresponsiveness (AHR), lung function decline and risk of asthma (18)(19)(20)(21)(22)(23)(24). Furthermore, in obesity, lung volume and tidal volume are reduced, thus promoting airway narrowing (20,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…One cohort study 23 of visceral fat and respiratory function did not exclude patients with COPD at baseline, so the relation of visceral fat to COPD incidence could not be established. Another cohort study 24 observed that a decline in respiratory function during follow-up was associated with a gain in visceral fat mass during follow-up but was not able to discern whether the gain in visceral fat mass was the cause or the consequence of the decline in respiratory function.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown age-related body composition changes in both men and women, notably that fat mass increases and muscle mass decreases with age [9,10]. Sarcopenia is an evolving concept and the current definition includes both a loss of muscle strength and loss of muscle mass [11].…”
mentioning
confidence: 99%